The European Union and interregionalism patterns of engagement - Doidge, Mathew (Ashgate Pub., 2011)
Exploring interregionalism beyond the core Europe-Asia partnerships, including the network of relations centred on ASEAN, this book is suitable for those engaged in consideration of interregional structures to understand how patterns of EU-centred interregional engagement are evident in the broader network of interregional relationships.